Academic Experience as Evaluation Material in Online Language Learning - Mayrita, Hastari; Boavida, Tito Guterres da Cruz (Jurnal Lingua Idea, 2023)
This study aims to explore the phenomena experienced by Lecturers and Students of the Indonesian Language Education Study Program in online learning during the Covid-19 period. The research method is qualitative with a phenomenological approach. Data collection was done through semi-structured interviews with five lecturers and eight students. Interview data was then analyzed within-case and cross-case. Researchers identified two problems related to what lecturers and students experienced in online learning: (1) barriers to using online learning media and (2) obstacles in presenting material and using learning methods. The results showed the lecturers' attitude in carrying out online learning was good by creating a fun online learning atmosphere. Unfortunately, the material provided was not understood by students. They complained about the material and its delivery by the lecturers. It was because the lecturers only provided material and assignments through e-learning. In addition, they only used discussion forums on e-learning to communicate. The researchers also identified that quota and internet network errors were the main problems encountered in online learning. This research can be used as material for evaluating the implementation of online academic activities, especially in language learning of the Indonesian Language Education Study Program. Data validity used member checks, triangulation, and peer debriefing.